SISTEM PENUNJANG KEPUTUSAN PROGRAM RASKIN SE-KOTA PALANGKARAYA - Parhusip, Jadiaman; Licantik, Licantik; Yulistria, Winda (Universitas Palangka Raya, 2015)
Limitations of the data and related information in an integrated population into the middle tolower barriers in implementing and coordinating programs both at the level of central government , localgovernment and with stakeholders. Therefore, the rural / urban poor record shall be eligible for assistanceRaskin (rice for the poor) which will cooperate with the data collection programs of social protectionofficer at the central statistical agency office Palangkaraya.The process of selecting candidates for assistance in Palangkaraya Raskin takes a decisionsupport system to give consideration in determining the prospective beneficiaries. Where the criteria forassistance Raskin consists of 10 criteria, namely : primary income, tenure occupied residential buildings,residential flooring type, wall type shelter, drinking water facilities, lighting facilities , a current cookingfuel , waste water facilities large, landfills feces, ownership of household assets. In building this websiteRaskin language used is PHP , and MySQL as database.Development method used is the waterfall method and decision support system with AnalyticalHierarchy Process (AHP). In this test has two methods: black box testing and the Turing test. Thisapplication helps in determining alternative Raskin recipients, potential recipients assist data managementand data management Raskin recipients selected from the recommendation.